2013
DOI: 10.1038/mp.2013.135
|View full text |Cite
|
Sign up to set email alerts
|

A ghrelin–growth hormone axis drives stress-induced vulnerability to enhanced fear

Abstract: Hormones in the hypothalamus-pituitary-adrenal (HPA) axis mediate many of the bodily responses to stressors, yet there is not a clear relationship between the levels of these hormones and stress-associated mental illnesses such as post-traumatic stress disorder (PTSD). Therefore, other hormones are likely to be involved in this effect of stress. Here we used a rodent model of PTSD in which rats repeatedly exposed to a stressor display heightened fear learning following auditory Pavlovian fear conditioning. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(163 citation statements)
references
References 92 publications
(116 reference statements)
13
149
1
Order By: Relevance
“…Some studies report that ghrelin relieves anxiety according to measures such as time spent in the open arm of an elevated plus maze (11,12,28). Others conclude that ghrelin acts in the amygdala to enhance fear and anxiety in rat models of posttraumatic stress disorder (15). The latter result supports our finding that chronic reduction of ghrelin promotes lower aggression, whereas chronic elevation has opposite effects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Some studies report that ghrelin relieves anxiety according to measures such as time spent in the open arm of an elevated plus maze (11,12,28). Others conclude that ghrelin acts in the amygdala to enhance fear and anxiety in rat models of posttraumatic stress disorder (15). The latter result supports our finding that chronic reduction of ghrelin promotes lower aggression, whereas chronic elevation has opposite effects.…”
Section: Discussionsupporting
confidence: 82%
“…Among BChE substrates that might drive differential responses to chronic social stress, ghrelin was the only plausible candidate (15). As BChE's catalytic activity with ghrelin had never been tested at physiological peptide concentrations (∼0.5 nM), we ran in vitro assays at that level and at 25 μM.…”
Section: Resultsmentioning
confidence: 99%
“…The acute stress response can alter circulating levels of many molecules, including interleukins and other immune-active factors 7 , hormones of the hypothalamic-pituitary-adrenal axis 8 , hormones in the sympathetic nervous system 9 , ghrelin 10 , endogenous opioids 11 , dopamine, and serotonin Stress responses not only alter the composition of the blood, but also represent a technical obstacle for blood sampling because of the constriction of vasculature via increased drive from the sympathetic nervous system. It becomes increasing difficult to obtain steady blood flow from a rat that is mounting an acute stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists for effects of both a single restraint event and repeated restraints on subsequent fear learning. Several studies have shown increased freezing upon exposure to a context previously paired with shock in rodents that have undergone brief (30 min-2 h) restraint (Cordero et al 2003;Rodriguez Manzanares et al 2005;Tronson et al 2010), whereas other studies utilizing repeated restraint have observed increased freezing upon exposure to a tone previously paired with shock (Meyer et al 2014;Suvrathan et al 2014;Baratta et al 2015). The degree to which restraint stress affects fear learning, generalization, extinction rate, or extinction retention differs, depending on the method and duration of restraint, the varying delays between the stress and fear conditioning and differences in the amount of shock utilized during conditioning (Miracle et al 2006;Andero et al 2011Andero et al , 2013Chauveau et al 2012).…”
Section: Stress-enhanced Fear Learning Modelsmentioning
confidence: 99%